Impaired kidney function is associated with lower quality of life among community-dwelling older adults - Artzi-Medvedik, Rada; Kob, Robert; Fabbietti, Paolo; Lattanzio, Fabrizia; Corsonello, Andrea; Melzer, Yehudit; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Mattace-Raso, Francesco; Tap, Lisanne; Gil, Pedro; Martinez, Sara Lainez; et al. (BMC Geriatrics, 2020)
Background: Quality of life (QoL) refers to the physical, psychological, social and medical aspects of life that are influenced by health status and function. The purpose of this study was to measure the self-perceived health status among the elderly population across Europe in different stages of Chronic Kidney Disease (CKD). Methods: Our series consisted of 2255 community-dwelling older adults enrolled in the Screening for Chronic Kidney Disease (CKD) among Older People across Europe (SCOPE) study. All patients underwent a comprehensive geriatric assessment (CGA), including included demographics, clinical and physical assessment, number of medications taken, family arrangement, Geriatric Depression Scale (GDS), Cumulative Illness Rating Scale, History of falls, Lower urinary tract symptoms, and Short Physical Performance Battery (SPPB). Estimated glomerular filtration rate (eGFR) was calculated by Berlin Initiative Study (BIS) equation. Quality of life was assessed by Euro Qol questionnaire (Euro-Qol 5D) and EQ-Visual Analogue Scale (EQ-VAS). The association between CKD (eGFR < 60, < 45 ml or < 30 ml/min/1.73m2) and low EQoL-VAS was investigated by multivariable logistic regression models. Results: CKD was found to be significantly associated with low EQoL-VAS in crude analysis (OR = 1.47, 95%CI = 1.16-1.85 for eGFR< 60; OR = 1.38, 95%CI = 1.08-1.77 for eGFR< 45; OR = 1.57, 95%CI = 1.01-2.44). Such association was no longer significant only when adjusting for SPPB (OR = 1.20, 95%CI = 0.93-1.56 for eGFR< 60; OR = 0.87, 95%CI = 0.64-1.18 for eGFR< 45; OR = 0.84, 95%CI = 0.50-1.42), CIRS and polypharmacy (OR = 1.16, 95%CI = 0.90-1.50 for eGFR< 60; OR = 0.86, 95%CI = 0.64-1.16 for eGFR< 45; OR = 1.11, 95%CI = 0.69-1.80) or diabetes, hypertension and chronic obstructive pulmonary disease (OR = 1.28, 95%CI = 0.99-1.64 for eGFR< 60; OR = 1.16, 95%CI = 0.88-1.52 for eGFR< 45; OR = 1.47, 95%CI = 0.92-2.34). The association between CKD and low EQoL-VAS was confirmed in all remaining multivariable models. Conclusions: CKD may significantly affect QoL in community-dwelling older adults. Physical performance, polypharmacy, diabetes, hypertension and COPD may affect such association, which suggests that the impact of CKD on QoL is likely multifactorial and partly mediated by co-occurrent conditions/risk factors.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Chronic kidney disease; Old adults; Quality of life